THE INFLUENCE OF PROFESSIONALISM, COMPETENCY, AND WORK EXPERIENCE ON AUDIT QUALITY AT THE PUBLIC ACCOUNTANT OFFICE IN MEDAN CITY - Fachruddin, Wan; Tjg, Yulia Syafriani (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2020)
This study aims to examine and analyze the effect of professionalism, competence and work experience on audit quality. This study uses an associative approach. The population in this study were all auditors who work at the Public Accounting Firm (KAP) in Medan City with a sample of 50 auditors . The sampling technique in this study used a convenience sampling technique. Collecting data used in this study using a questionnaire. The data analysis technique was carried out by using multiple linear regression analysis. The results showed simultaneously and partially professionalism, competence and work experience had a significant effect on audit quality .